EFUSI PLEURA MALIGNA: DIAGNOSIS DAN PENATALAKSANAAN TERKINI - Ngurah Rai, I B (journal of internal medicine; Vol. 10, No. 3 September 2009)
Malignant pleural effusions (MPE) are an important complication for patients with intra and extrathoracic malignancies. MPE are also a complication of far advanced malignancies or as the initial manifestations of an underlying malignancy, with more than 150.000 cases/year in America. Median survival after diagnosis of an MPE is about 4 months. Although almost every tumor can cause it, more than 75% of MPE caused by malignancies at lung, breast, ovaries, mesotheliomas and lymphomas. The standard management approach begins with a diagnostic and or therapeutic thoracentesis. New imaging modalities help us to diagnose MPE, however positive cytologic conÞ rmation is necessary to establish a diagnosis. But, there are difÞ culties to Þ nd the etiology and deal with rapid recurrences of MPE. It is where several biomarkers took place in diagnosing MPE. Managements of an MPE remain palliative. Several options include thoracenteses, pleurodesis, continuous outpatient drainage with indwelling catheter, and pleuroperitoneal shunting. Recent studies focused on molecular marker and inß ammatory cytokine as a diagnostic tool and target therapy for MPE. Many studies look for the role of EGFR (Epidermal Growth Factor Receptor), MCP-1 (monocyte chemoattractant protein-1), VEGF (vascular endothelial growth factor), and TNF-  in diagnosing and possibly treat MPE.
Keywords: malignant pleural effusion, etiology diagnostic, deÞ nitive treatment